2021
DOI: 10.1007/s00415-021-10600-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of status epilepticus in persons with epilepsy is determined by sex, epilepsy classification, and etiology: a single center cohort study

Abstract: Background Status epilepticus (SE) can occur in persons with or without epilepsy and is associated with high morbidity and mortality. Methods This survey aimed to record self-reported frequency of SE in persons with epilepsy, its association with clinical characteristics and patient level of information on SE and rescue medication. 251 persons with epilepsy at a tertiary epilepsy center were included in the study. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…13 Neurological comorbidities were found in 21.7% of patients and non-neurologic systemic comorbidities varied, consistent with the profile reported in a high complexity German center. 22 The majority of our patients had one brain image (57.6%), a higher percentage when compared with the Polish study already mentioned, which reported that brain imaging was performed in less than 20% of patients, and brain magnetic resonance was performed only in 1 patient. As electroencephalography, more recordings performed in our study (32.6%) when compared with the by Stawińska-Witoszyńska (11.1%).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…13 Neurological comorbidities were found in 21.7% of patients and non-neurologic systemic comorbidities varied, consistent with the profile reported in a high complexity German center. 22 The majority of our patients had one brain image (57.6%), a higher percentage when compared with the Polish study already mentioned, which reported that brain imaging was performed in less than 20% of patients, and brain magnetic resonance was performed only in 1 patient. As electroencephalography, more recordings performed in our study (32.6%) when compared with the by Stawińska-Witoszyńska (11.1%).…”
Section: Discussionmentioning
confidence: 47%
“…However, when considering only the hospitalized population, this subgroup would account for 18.69%, a proportion that is lower than reported in a recent study in a German population explicitly aimed at finding patients with a history of status epilepticus over their lifetime and which reported an amount of 34.6% of the total number of patients. 22 It is worth highlighting that no questions about a history of status epilepticus was explicitly asked during outpatient assessments, which would explain, at least in part, the low percentage of occurrence of this phenomenon in our group of patients, given that only the hospitalized population would be represented.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, biological sex and sex-specific thresholds as estimates of organ dys/function (SAPS II) are not included in ICU risk assessment tools, and may thus underestimate illness severity in women, given their lower thresholds in most biomarkers. Accordingly, earlier studies have described female sex as an important promotor of the emergence of SE in patients with epilepsy [ 3 ] and that female sex is associated with a higher mortality in SE [ 32 ]. This is a serious and worrisome hypothesis which warrants further studies, including careful reassessment of contemporary risk assessment tools in order to provide equal opportunities to men and women [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies regarding the role of sex on the emergence of SE, its treatment, course, and outcome are scarce. Although some studies have suggested that female sex may be a risk factor for the development of SE in patients with epilepsy [ 3 ], and that women may receive less aggressive care than men regardless of illness severity [ 4 ], other studies have reported conflicting findings. For example, early studies suggested that the incidence of SE was lower in women than men, and other studies found no significant sex-related differences regarding the incidence of SE [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASM was prescribed to control seizures in the acute phase, and a larger number of ASMs was related to increased seizure severity and worse autoimmune processes in the acute phase, which may contribute to the development of epilepsy after the acute phase. It was recently reported that patients with epilepsy who had a history of status epilepticus were more likely to receive a larger number of ASMs than those without a history of status epilepticus ( 21 ). Thus, it is not surprising that in AE patients, a larger number of ASMs may be related to the occurrence of status epilepticus, which was also identified as a risk factor for the development of epilepsy in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%